Mujeres en la producción artística española del siglo XX - Muñoz López, Pilar (Cuadernos de Historia Contemporánea, 2006)
The paper displays women’s participation in Plastic Arts in Spain in the 20th Century. First it exposes the situation during the first part of century. It reveals some distinguished artists for the period prior to the Civil War artist men. In the years of the Second Republic and the Civil War it shows the participation of women artists in political posters and illustrations pictures’ production. After the Franco’s victory, and though ideology was constricting them to family life, women continued their participation in plastic arts. Finally the artistic productions of women have evolved in parallel with the advancement of feminine condition in the western world, althongh they hare not obtained total equality with respecto.